GAYA BAHASA (STYLE) DALAM BUKU DONGENG KLASIK 5 BENUA KARYA ASTRI DAMAYANTI - David Adikara, S.Pd. (Pendidikan Bahasa dan Sastra Indonesia, 2018)
The specificity of language in fairy tales were characterized by an unusual choice of words when viewed from the practical language. The form of election irregularity words or diction, sentence structure, and style of the language. Based on the above background, the purpose of this study was to describe (1) the use of diction, (2) the structure of the sentence, and (3) the dominant language styles are used in the bookof5 Benua Classic FablebyDamayanti. The method used in this study is a descriptive qualitative method. This research resulted in, (1) the use of diction include: (a) the common word, (b) the special word, (c) the meaning of denotation, and (d) the connotations. (2) The use of sentence structure includes: (a)thesingle sentence, (b) thecompound sentence, (c)theactive sentence, and (d) the passive voice. (3) The use of language dominant force include: (a) stylistic comparisons include: personification, anticipation or prolepsis, and aleogori manifold fable; (B) the language style of contention include: hyperbole, climax and anticlimax; (C) the language style of engagement include: antonomasia and epithets; and (d) the language style looping include: anaphora and epistrofa.